Implementasi Fungsi Manajemen Pada Program Tahfidz Al-Qur’an di Madrasah - Pratama, Agung Setyo; Al Rosid, Moh. Harun (Universitas Sarjanawiyata Tamansiswa, 2025)
The main objective of this study is to examine the tahfidz (memorization) program of the Qur'an at MTs. Al Furqon Siliragung Banyuwangi which implements management functions. The implementation of management functions into the Qur'an memorization curriculum is a transformation of the madrasah in developing its education. This study uses a qualitative approach based on a case study design. The research informants include the head of the madrasah, the deputy for curriculum, and the homeroom teacher. Data collection through participant observation, in-depth interviews, and documentation. The theory of Miles, Huberman, and Saldana is used in data analysis through data condensation, data presentation, and drawing conclusions/verification. Test the validity of the data with reliability, confirmability, and credibility. Furthermore, the researcher checks the adequacy of references, member checking, triangulation, peer discussion, and continuous monitoring in the accuracy of the data. Based on the research results, there are three steps that can be taken to plan and implement a successful Al-Qur'an memorization program, namely: 1) setting goals through discussions at regular meetings, determining what materials are needed, and identifying educator needs. 2) building an organizational structure that pays attention to the educator's field of expertise. 3) implementing the program through a learning process that follows a system agreed upon by the management and educators, using innovative strategies to improve memorization methods, namely Talqin and Talaqqi, 4). Pengawasan on through the use of direct observation of learning activities, monitoring memorization progress, and frequent assessment of the process and results.